A carbon quantum dots‐enhanced chemiluminescence method for the determination of gallic acid in food samples. Issue 7 (6th March 2018) - Chen, Xiaoxia; Zhang, Junmei; Han, Suqin; Liu, Haizhen; Du, Yao
Abstract : In this work, we show that gallic acid can significantly inhibit the chemiluminescence (CL) intensity of carbon quantum dots (CQDs)‐enhanced K3 Fe(CN)6 –luminol system. Under optimum conditions, the decrease in the CL intensity is proportional to the concentration of gallic acid over the range 0.01–1.0 μM, and the detection limit is 1.0 nM. The relative standard deviation of repeated intraday and interday determinations of gallic acid was 1.2–4.2%. This method was successfully applied to the determination of gallic acid in food samples, with recoveries in the range 94.0–103.0%. A possible mechanism of CL is discussed. Abstract : A carbon quantum dots‐enhanced chemiluminescence method (CL) is successfully applied for the determination of gallic acid in food samples. A possible mechanism of CL is discussed.